Evaluation of the obesity genes FTO and MC4R and the type 2 diabetes mellitus gene TCF7L2 for contribution to stroke risk: the Mannheim-Heidelberg stroke study - Winter, Yaroslav; Back, Tobias; Scherag, André; Linseisen, Jakob; Rohrmann, Sabine; Lanczik, Oliver; Hinney, Anke; Scherag, Susann; Neumaier, Michael; Ringleb, Peter A.; Dodel, Richard; Hebebrand, Johannes (Obesity facts, 2011)
Objective: Studies evaluating genetic markers for vascular risk and risk of stroke are limited, and none of them evaluated obesity genes. The objective was to investigate the genetic markers related to obesity genes FTO and MC4R and the gene of type 2 diabetes mellitus TCF7L2 for their contribution to risk of stroke and transient ischemic attacks (TIA). Methods: We recruited 379 consecutive patients with stroke/TIA and 379 healthy population-based controls. The single-nucleotide polymorphisms (SNPs) rs9937053 (FTO), rs2229616 (MC4R V103I), rs17782313 (188kb downstream of MC4R), and rs7903146 (TCF7L2) were evaluated for association with stroke using logistic regression analyses. Results: The odds ratios for stroke/TIA were 1.14 (95%CI 0.91–1.42) for rs9937053/FTO, 1.11 (95%CI 0.49–2.51) for rs2229616/MC4R, 1.05 (95%CI 0.82–1.3) for rs17782313/MC4R, and 0.99 (95%CI 0.78–1.25) for rs7903146/TCF7L2. Further exploration revealed that male patients with the T allele of rs7903146/TCF7L2 had a worse clinical outcome compared with male patients carrying the C allele. Conclusion: The observed trends of obesity risk alleles for risk of stroke/TIA as well as the possible sex-specific differences in clinical outcomes found for the TCF7L2 (rs7903146) require replication in future studies. Our study demonstrates that candidate gene studies for common stroke may benefit from focusing on polymorphisms that predispose to vascular risk.